A new species of Cosmocercella parasite of Diaglena spatulata and Triprion petasatus (Anura: Hylidae) from Mexico, based on new morphological information for the genus - Mata-López, Rosario; Guillén-Hernández, Sergio; León-Règagnon, Virginia (Zootaxa, 2008)
A new species of Cosmocercella as a parasite of the hylid frogs Diaglena spatulata and Triprion petasatus is herein described. The new species most closely resembles C. haberi and C. anothecae, both species distributed in Mexico. Cosmocercella diaglenae n. sp. differs from these species in the arrangement of the caudal papillae, and mainly in the presence and size of the first pair of papillae situated anteriorly to the anus, but it also differs by the distance between the second and third pairs of plectanes, by the length of the spicules and gubernaculum, by the size and form of the pharynx, as well as the esophageal bulb length-width ratio in females and finally by having larger eggs. In order to find additional taxonomic characteristics to distinguish among species, a morphometrical study was conducted.